What makes a mental state feel like a memory: feelings of pastness and presence - Rosen, Melanie; Barkasi , Michael (Estudios de Filosofía, 2021)
The intuitive view that memories are characterized by a feeling of pastness, perceptions by a feeling of presence, while imagination lacks either faces challenges from two sides. Some researchers complain that the “feeling of pastness” is either unclear, irrelevant or isn’t a real feature. Others point out that there are cases of memory without the feeling of pastness, perception without presence, and other cross-cutting cases. Here we argue that the feeling of pastness is indeed a real, useful feature, and although this feeling does not define memory ontologically, it is a characteristic marker which helps us easily categorise a mental state first-personally. We outline several cognitive features that underlie this experience, including the feeling of past accessibility, ergonomic significance, immersion, objectivity and mental strength. Our account is distinctly phenomenal, rather than doxastic, although our web of beliefs may contribute to this experience.